2022
DOI: 10.1101/2022.06.11.495745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low diversity and microdiversity of comammox bacteria in wastewater systems suggests wastewater-specific adaptation within the Ca. Nitrospira nitrosa cluster

Abstract: Studies have found Ca. Nitrospira nitrosa-like bacteria to be the principal or sole comammox bacteria in nitrogen removal systems for wastewater treatment. In contrast, multiple populations of strict ammonia and nitrite oxidizers co-exist in similar systems. This apparent lack of diversity is surprising and could impact the feasibility of leveraging comammox bacteria for nitrogen removal. We used full-length 16S rRNA gene sequencing and genome-resolved metagenomics to compare population-level (i.e., species) d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 107 publications
1
5
3
Order By: Relevance
“…Our previous work demonstrated that comammox bacteria are most prevalent in nitrogen removal systems treating wastewater with an attached growth phase or long solids retention times, and they often co-occur with strict AOB and Nitrospira-NOB 8 . Further, a large portion of comammox bacteria detected in wastewater systems, including those in our past studies 8,9 , belong to clade A1 comammox bacteria and are affiliated with Ca. Nitrospira nitrosa-like populations [10][11][12] .…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Our previous work demonstrated that comammox bacteria are most prevalent in nitrogen removal systems treating wastewater with an attached growth phase or long solids retention times, and they often co-occur with strict AOB and Nitrospira-NOB 8 . Further, a large portion of comammox bacteria detected in wastewater systems, including those in our past studies 8,9 , belong to clade A1 comammox bacteria and are affiliated with Ca. Nitrospira nitrosa-like populations [10][11][12] .…”
Section: Introductionmentioning
confidence: 63%
“…MAGs associated with Brocadia (n=2) and Nitrospira (n=3) were obtained from biomass attached to IFAS media even though anammox bacteria were not found in our past study 8,9 . Nitrospira and Brocadia MAGs represented 6.53  0.34 % and 6.25  1.33% of total reads in the sample.…”
Section: Dissolved Oxygen Dependent Nitrification and Nitrogen Loss O...mentioning
confidence: 69%
See 3 more Smart Citations